TURN TAKING USED IN ENGLISH EDUCATION ZOOM VIRTUAL CLASSROOM - Indah Wijayanti (JAMBI-ENGLISH LANGUAGE TEACHING, 2023)
This research aimed to analyze the turn taking strategies and how the teacher and the students achieve turn taking process in virtual class. This research was conducted at one public university in Jambi. The researcher used video recording as the data of this research. There were three videos recorded in this study they consisted of three different courses in English education. This research employed qualitative study to describe the turn taking strategies and which were expressed in Zoom virtual classes. In analyzing the data, the researcher used Stenstrom’s theory to classify the turn taking strategies into three categories such as Taking the turn strategy, Holding the turn strategy, and Yielding the turn strategy. The results show that the most dominant turn taking strategy is Holding the turn strategy and the least used is Taking the turn strategy. By changing the medium in the conversation, it also changes how to achieve turn-taking in conversation. Within the Zoom virtual class, there are many features that can help speakers and listeners achieve turn taking such as audio channel, video channel, chat channel, and raise hand feature. Key Words: Turn Taking, Virtual Class, English Education, Qualitative